Obsessive-compulsive symptoms in patient with schizophrenia: The influence of disorganized symptoms, duration of schizophrenia, and drug resistance - Panov, Georgi; Panova, Presyana (Frontiers in Psychiatry, 2023)
Background Schizophrenia is a chronic mental disorder with a many-faced clinical presentation. Obsessive–compulsive symptoms are often part of it. The characteristics of the clinical picture and the course of schizophrenia are factors related to both the resistance and the manifestation of obsessive–compulsive symptoms. Our study aims to establish the relationship between the peculiarities of the schizophrenia process and the influence of resistance on the expression of obsessive–compulsive symptoms. Methods A study was conducted on 105 patients with schizophrenia. Of them, 39 are men and 66 are women. The evaluation of the effectiveness of the treatment showed that 45 were resistant to the applied therapy, while the remaining 60 responded. Clinical assessment of patients was performed using the Positive and Negative Syndrome Scale (PANSS) and Brief Psychiatric Rating Scale (BPRS). Assessment of obsessive–compulsive symptoms (OCS) was conducted with the Dimensional obsessive–compulsive symptoms scale (DOCS). Results In 34% of all patients, we found clinically expressed obsessive–compulsive symptoms. In 40% of the patients with resistance, we found clinically expressed obsessive–compulsive symptoms, which are within the range of moderately expressed. In 30% of the patients in clinical remission, we found obsessive–compulsive symptoms, but mildly expressed. We found a statistically significant relationship between the severity of OCS and the disorganized symptoms and the duration of the schizophrenia process. No differences were found in the expression of OCS in patients of both sexes. Conclusion We registered both an increased frequency and an increased expression of obsessive–compulsive symptoms in patients with resistant schizophrenia. These symptoms were positively associated with disorganized symptoms and duration of schizophrenia. No relationship was established with the positive, negative symptoms, as well as with the gender distribution.